Optimal destabilization of cartels - Ludwig von Auer; Tu Anh Pham (Journal of Regulatory Economics, 2021)
This paper introduces an oligopoly model that includes three actors: a cartel (comprising two or more firms that operate like one merged company), a group of competing fringe firms, and a welfare maximizing antitrust authority. The cartel is the Stackelberg quantity leader and the fringe firms are in Cournot competition with respect to the residual demand. The cartel is internally stable if none of its member firms finds it profitable to become a fringe firm. The antitrust authority can destabilize the cartel in the sense of making the cartel internally instable. To this end, the antitrust authority has three policy instruments at its disposal: its own effort, a fine for detected cartels, and a leniency program for cartel members that cooperate with the authority. Taking into account that the use of these instruments is not costless for society, a unique optimal antitrust policy is derived. The analysis reveals that both, the optimal force and mix of the antitrust authority's policy depend on market characteristics such as the efficiency of the authority's operations, the public respect for the rule of law, the ethical standards of the firms' managers, the market volume, and the number of firms operating on the market.
Keywords: L13; L41; 330; Antitrust; Stability; Leadership model; Oligopoly; Fringe firms; Leniency